Mechanisms and functional implications of ZDHHC5 in cellular physiology and disease - Huicong Liu; Shuo Wen; Chang Xu; Xiaohong Kang; Eryan Kong (Journal of Lipid Research)
Post-translational lipid modification by palmitoylation is a reversible process crucial for maintaining cellular functionality. The palmitoyl acyltransferase zinc finger Asp-His-His-Cys motif-containing 5 (ZDHHC5) has garnered significant attention due to its roles in neurodegenerative diseases, oncogenesis, and cardiac function. ZDHHC5 recognizes substrates through diverse mechanisms and its activity is regulated by multiple factors. Highly expressed in the brain, liver, and heart, ZDHHC5 exerts regulatory functions in various cellular processes through self-regulation and substrate palmitoylation. This review summarizes ZDHHC5's regulatory roles in the nervous system, lipid metabolism and oncogenesis, highlighting its potential as a therapeutic target for neurological, lipid metabolic diseases, and cancer due to its involvement in diverse cellular processes and disease-associated dysfunctions.